Slovakia: Neverending Story About Fiscal Responsibility - Štrkolec, Miroslav (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter addresses the issue of budget management in Slovakia. The importance of this issue for the state is emphasised by the fact that the essential aspects constituting the foundations of public finances are directly regulated in the Constitution of the Slovak Republic. The Constitution regulates not only the basic rules for the creation and content of public budgets but also the powers of the supreme constitutional bodies in this field. An extremely important area of regulation is the prevention of excessive deficit and excessive state debt. For this purpose, significant constitutional changes took place in Slovakia, which led to the creation of a new constitutional body, the Council for Budget Responsibility. Similarly, responsible budget management is equally important at the local self-government level, where the legislation also establishes several brakes to prevent deficit budgeting and the indebtedness of self government. In this chapter, we discuss these complex issues in detail and highlight the key aspects of Slovak legal regulation. At the end of the chapter, we deal with the current challenges for budget management in Slovakia, which are connected to the growing deficit and the associated need to find new sources of income for public budgets, as well as the reduction of public expenditures.Keywords: public finance in Slovakia, budgetary rules, budgetary responsibility, state debt, Supreme audit office, Council for Fiscal Responsibility